2023
DOI: 10.1039/d3ta02115g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-support interactions alter the active species on IrOx for electrocatalytic water oxidation

Abstract: Constructing metal-support interaction (MSI) is a widely concerned strategy to promote the electrocatalytic performance of oxygen evolution reaction (OER). However, studies helping to understand the electrocatalytic behavior of reactive centers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These observations suggest the presence of another species at more anodic potentials. The band at ∼1146 cm –1 falls into the range where superoxo species are known to absorb. First, we excluded the possibility that the band arises from an irreversibly adsorbed catalytic species on the surface. Following the spectroelectrochemical experiments with the Ir-dimer (Figure A), we conducted spectroelectrochemical experiments with the same electrode but without the Ir-dimer in solution (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest the presence of another species at more anodic potentials. The band at ∼1146 cm –1 falls into the range where superoxo species are known to absorb. First, we excluded the possibility that the band arises from an irreversibly adsorbed catalytic species on the surface. Following the spectroelectrochemical experiments with the Ir-dimer (Figure A), we conducted spectroelectrochemical experiments with the same electrode but without the Ir-dimer in solution (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…6 Noble metal (Ir and Ru) based electrocatalysts show a good OER activity; however, the scarcity and high cost seriously restrict their wide application. 7,8 In recent years, researchers have revealed that transition metal-based oxides, 9–11 sulfides, 12,13 phosphides, 14,15 carbides 2,16,17 and alloys 18,19 also show promising catalytic properties for both the HER and OER, which are expected to replace precious metal oxide electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Nevertheless, given the scarcity and high price of Ir metal, it is desirable to develop high-performance Ir-based OER catalysts with minimal usage of precious Ir metal. [6][7][8][9] To date, significant strategies have been applied to enhance the OER performance of Ir-based catalysts, such as introducing a strong metal-support interaction, 10,11 constructing alloys with other metals, 12,13 and modulating the surface atomic structure of the catalysts. 14,15 Recently, several studies have revealed that the surface charge properties of catalysts will have an essential impact on the adsorption/desorption of reactants at the active sites of catalysts, since the electrocatalytic reactions are carried out under external potentials.…”
mentioning
confidence: 99%